Codon Optimization of Insect Odorant Receptor Genes May Increase Their Stable Expression for Functional Characterization in HEK293 Cells - Roberts, Rebecca E.; Yuvaraj, Jothi Kumar; Andersson, Martin N. (Frontiers in Cellular Neuroscience, 2021)
Insect odorant receptor (OR) genes are routinely expressed in Human Embryonic Kidney (HEK) 293 cells for functional characterization (“de-orphanization”) using transient or stable expression. However, progress in this research field has been hampered because some insect ORs are not functional in this system, which may be due to insufficient protein levels. We investigated whether codon optimization of insect OR sequences for expression in human cells could facilitate their functional characterization in HEK293 cells with stable and inducible expression. We tested the olfactory receptor co-receptor (Orco) proteins from the bark beetles Ips typographus (“Ityp”) and Dendroctonus ponderosae (“Dpon”), and six ItypORs previously characterized in Xenopus laevis oocytes and/or HEK cells. Western blot analysis indicated that codon optimization yielded increased cellular protein levels for seven of the eight receptors. Our experimental assays demonstrated that codon optimization enabled functional characterization of two ORs (ItypOR25 and ItypOR29) which are unresponsive when expressed from wildtype (non-codon optimized) genes. Similar to previous Xenopus oocyte recordings, ItypOR25 responded primarily to the host/conifer monoterpene (+)-3-carene. ItypOR29 responded primarily to (+)-isopinochamphone and similar ketones produced by fungal symbionts and trees. Codon optimization also resulted in significantly increased responses in ItypOR49 to its pheromone ligand (R)-(−)-ipsdienol, and improved responses to the Orco agonist VUAA1 in ItypOrco. However, codon optimization did not result in functional expression of DponOrco, ItypOR23, ItypOR27, and ItypOR28 despite higher protein levels as indicated by Western blots. We conclude that codon optimization may enable or improve the functional characterization of insect ORs in HEK cells, although this method is not sufficient for all ORs that are not functionally expressed from wildtype genes.